A New Acyl-homoserine Lactone Molecule Generated by Nitrobacter winogradskyi - Shen, Qiuxuan (Sci Rep, 2016)
It is crucial to reveal the regulatory mechanism of nitrification to understand nitrogen conversion in agricultural systems and wastewater treatment. In this study, the nwiI gene of Nitrobacter winogradskyi was confirmed to be a homoserine lactone synthase by heterologous expression in Escherichia coli that synthesized several acyl-homoserine lactone signals with 7 to 11 carbon acyl groups. A novel signal, 7, 8-trans-N-(decanoyl) homoserine lactone (C10:1-HSL), was identified in both N. winogradskyi and the recombined E. coli. Furthermore, this novel signal also triggered variances in the nitrification rate and the level of transcripts for the genes involved in the nitrification process. These results indicate that quorum sensing may have a potential role in regulating nitrogen metabolism.